Self-Organization of 𝐊+-Crown Ether Derivatives into Double-Columnar Arrays Controlled by Supramolecular Isomers of Hydrogen-Bonded Anionic Biimidazolate Ni Complexes - Makoto Tadokoro; Kyosuke Isoda; Yasuko Tanaka; Yuko Kaneko; Syoko Yamamoto; Tomoaki Sugaya; Kazuhiro Nakasuji (Journal of Nanotechnology)
Anionic tris (biimidazolate) nickelate (II) ([Ni(Hbim)3]−), which is a hydrogen-bonding (H-bonding) molecular building block, undergoes self-organization into honeycomb-sheet superstructures connected by complementary intermolecular H-bonds. The crystal obtained from the stacking of these sheets is assembled into channel frameworks, approximately 2 nm wide, that clathrate two cationic K+-crown ether derivatives organised into one-dimensional (1D) double-columnar arrays. In this study, we have shown that all five cationic guest-included crystals form nanochannel structures that clathrate the 1-D double-columnar arrays of one of the four types of K+-crown ether derivatives, one of which induces a polymorph. This is accomplished by adaptably fitting two types of anionic [Ni(Hbim)3]− host arrays. One is a ΔΛ−ΔΛ−ΔΛ⋯ network with H-bonded linkages alternating between the two different optical isomers of the Δ and Λ types with flexible H-bonded [Ni(Hbim)3]−. The other is a ΔΔΔ−ΛΛΛ⋯ network of a racemate with 1-D H-bonded arrays of the same optical isomer for each type. Thus, [Ni(Hbim)3]− can assemble large cations such as K+ crown-ether derivatives into double-columnar arrays by highly recognizing flexible H-bonding arrangements with two host networks of ΔΛ−ΔΛ−ΔΛ⋯ and ΔΔΔ−ΛΛΛ⋯.